1993
DOI: 10.1080/00224545.1993.9712145
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pet Dogs in Casual Conversations of Elderly Adults

Abstract: Casual conversations were recorded as elderly persons routinely walked their dogs through a familiar mobile home park in the United States. Control observations included walks without dogs by owners and non-owners of dogs. All owners talked to and about their dogs. Transcribed conversations indicated that dogs were a primary focus of conversation. A majority of sentences to dogs were imperatives; the owners were instructing the dogs. Dog owners frequently included dogs' names or nicknames in their sentences wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 24 publications
2
62
0
1
Order By: Relevance
“…Dog walkers are more likely to experience social contact and conversation than people walking alone (McNicholas & Collis, 2000). But dogs can also serve as a topic of casual conversation for walkers, even when not accompanying their owner, as found in the conversation analysis of a dog-walking experiment (Rogers, Hart, & Boltz, 1993). Another positive effect of pets is seen when familial relationships grow even stronger as a consequence of striving to meet the daily requirements of their beloved pets.…”
Section: Social Supportmentioning
confidence: 99%
“…Dog walkers are more likely to experience social contact and conversation than people walking alone (McNicholas & Collis, 2000). But dogs can also serve as a topic of casual conversation for walkers, even when not accompanying their owner, as found in the conversation analysis of a dog-walking experiment (Rogers, Hart, & Boltz, 1993). Another positive effect of pets is seen when familial relationships grow even stronger as a consequence of striving to meet the daily requirements of their beloved pets.…”
Section: Social Supportmentioning
confidence: 99%
“…It has been argued that, compared with non-owners, those who own pets are likely to have lower levels of neuroticism and higher levels of both extraversion and attachment to humans [13][14][15][16] . However, support for this hypothesis is limited, and the studies that have explored this issue have considered only undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…Since research has clearly identified the lack of supportive social companionship networks as one of the leading causes of depression, stress and suppression of the immune system (Serpell 1986(Serpell /1996, considering animal companionships in this context as a suitable alternative could be useful (Hart 2006). Through the stimulation of conversations, providing opportunities to meet people while out walking, encouraging people to interact through shared interests and providing a topic for conversation, dogs act as social catalysts (Hart 2006;Hunt et al 1992;McNicholas and Collis 2000;Rogers et al 1993). The more recent literature says that, due to the boundless capacity to forgive that is innate in animals, as well as their ability to show adoration, attention, forgiveness and unconditional love, interaction with and ownership of animals is beneficial (Bustad and Hines 1983;McNicholas et al 2005).…”
Section: Contact With Animalsmentioning
confidence: 99%